Compensation for balance disorders: analysis of this multifactorial process - Philippe Perrin; Art Mallinson; Neil Longridge; Enrico Armato; Mans Magnusson; Georges Dumas; Nicolas Perrin; Pierre Denise; Paolo Gargiulo; Hannes Petersen; Christian Beyaert (European Journal of Translational Myology)
The European Society for Clinical Evaluation of Balance Disorders (ESCEBD), based in Nancy, France, has been meeting yearly since 2005 to discuss equilibrium-related themes that are not yet clearly defined or standardized. One of our latest discussions was with regard to outlining strategies of internal and external compensation that may be used to cope with balance disorders. A Committee was elected to discuss the mechanisms of compensation that may be involved in coping with balance system disorders. Compensation, referring to the immediate or short-term adaptive mechanisms that are used to counterbalance the effects of deficiencies that disrupt balance maintenance, can include alternative strategies, resources, or environmental supports to overcome deficits or challenges associated with a deficiency. The strategies can be internal (i.e. utilizing the individual’s own multi-sensory neural integration, motor, and cognitive resources) or external (i.e. modifying the environment, or using assistive or adaptive devices) to reduce fall hazard and enhance safety. This report focuses principally on internal compensation, generated by sensorimotor processes of the central nervous system (CNS) in response to impairment of either sensory information (e.g. vestibular pathologies), the musculoskeletal system (e.g. lower limb amputation and myopathies) or the CNS itself (e.g. upper motor neuron syndrome). The multifactorial process of compensation may explain the limitations encountered by the CNS in compensating for complex bodily impairments and may also limit our understanding of how the CNS adapts to balance disorders. Newly developed devices, such as wearable sensory substitution devices, are on the horizon as possible tools.